Teaching English Idioms for the First Year Students in Non-Linguistic Universities: On the Example of Technical and Economic Universities - Zulfikorova, Azizakhon (Pindus Journal of Culture, Literature, and ELT, 2021)
Compiling an effective English lesson focusing on idioms for the first year students of technical and economic universities is a great challenge even for the experienced language teachers. This is a multi-dimensional process and requires to take into account a number of variables. This paper uses theoretical-comparative analysis to examine the specific features of teaching English for first-year students of technical and economic specialties with the focus on teaching English idioms. The research also aims to reveal some effective pedagogical approaches, methods, and teaching techniques on the issue. The research results reaffirm the conclusions of some previous studies stating that practical use of English idioms prevails over the theoretical knowledge about them in the spheres of technology and economy. The novelty of the research is in the results of the theoretical-comparative analysis, which has shown that the communicative approach, method of relativity to the future profession of the students, and such techniques as the step-by-step limited introduction of new idioms, thematic derivations, and profession-oriented discussions are potentially most effective ways of teaching idioms and idiomatic expressions for the students engaged in the technology and economy spheres. Moreover, diversity of levels of first-year students’ language skills and motivational problems of most technical and some economic students should also be taken into consideration.